The caecal microbiota promotes the acute inflammatory response and the loss of the intestinal barrier integrity during severe Eimeria tenella infection - Tomal, Florian; Sadrin, Guillaume; Gaboriaud, Pauline; Guitton, Edouard; Sedano, Laura; Lallier, Nathalie; Rossignol, Christelle; Larcher, Thibaut; Rouille, Elodie; Ledevin, Mireille; Guabiraba, Rodrigo; Silvestre, Anne; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Coccidiosis, a disease caused by intestinal apicomplexan parasites Eimeria, is a threat to poultry production. Eimeria tenella is one of the most pathogenic species, frequently causing a high prevalence of opportunistic infections. Objective The objective of this study is to investigate the role of the microbiota in the pathogenesis of severe Eimeria tenella infection. Methods We have previously shown that microbiota can promote parasite development. To study the effect of the microbiota on the pathogenesis of this infection, we used an experimental condition (inoculum of 10 000 oocysts E. tenella INRAE) in which the parasite load is similar between germ-free and conventional broilers at 7 days post-infection (pi). Thirteen conventional and 24 germ-free chickens were infected. Among this latter group, 12 remained germ-free and 12 received a microbiota from conventional healthy chickens at 4 days pi. Caeca and spleens were collected at 7 days pi. Results Our results demonstrated caecal lesions and epithelium damage in conventional chickens at 7 days pi but not in germ-free infected chickens. Administration of conventional microbiota to germ-free chickens partially restored these deleterious effects. At day 7 pi, both infected conventional and germ-free chickens exhibited increased gene expression of inflammatory mediators, including IL15, IFNγ, TNFα and the anti-inflammatory mediator SOCS1, whereas the inflammatory mediators CXCLi2, CCL20, IL18, CSF1, NOS2, PTGS2, IL1β, IL6, the receptor CCR2, and the anti-inflammatory mediators TGFβ1 and IL10 were upregulated only in infected conventional chickens. Notably, the IL18, PTGS2 gene expression was significantly higher in the infected conventional group. Overall, the inflammatory response enhanced by the microbiota might be in part responsible for higher lesion scores. Epithelial tight junction protein gene expression analysis revealed a significant upregulation of CLDN1 with the infection and microbiota, indicating a potential loss of the intestinal barrier integrity. Conclusion These observations imply that, during E. tenella infection, the caecal microbiota could trigger an acute inflammatory response, resulting in a loss of intestinal integrity. Increase in bacterial translocation can then lead to the likelihood of opportunistic infections. Hence, modulating the microbiota may offer a promising strategy for improving poultry gut health and limiting caecal coccidiosis.